5 - World Bank Development Policies and Poverty Alleviation in Africa - Onwuka, Emmanuel Chike (Africa Development, 2006)
This paper looks at how World Bank policies affect the outcomes of efforts at alleviating widespread poverty in Africa. It questions the repercussion of these policies on the stability of African economies by analyzing the survey of the literature. From the evidence gathered from Africa and specific countries on the continent, the paper shows that the World Bank-supported adjustment reforms exacerbate rather than reduce poverty as they deal with growth-related prob- lems at the expense of human-centred or development associated measures; thus reinforcing the concerns that the reforms are an ineffective poverty allevia- tion instrument. Nevertheless, structural reforms could help push African econo- mies forward on condition that poverty reduction and not accounting records is their point of reference. That way, human development, which is the key to unlock Africa’s potential, would take its deserved place on the continent’s agenda.